Real-time observation of the effect of oxygen storage materials on Pd-based three-way catalysts under ideal automobile exhaust conditions: an operando study. Issue 18 (5th August 2021) - Asakura, Hiroyuki; Hosokawa, Saburo; Beppu, Kosuke; Tamai, Kazuki; Ohyama, Junya; Shishido, Tetsuya; Kato, Kazuo; Teramura, Kentaro; Tanaka, Tsunehiro
Abstract : The dynamic behavior of Pd species and the CeO2 support of 1 wt% Pd/Al2 O3 and Pd/CeO2 catalysts during three-way catalysis was examined in real time with operando multi-probe analysis. Abstract : The dynamic behavior of Pd species and the CeO2 support of 1 wt% Pd/Al2 O3 and Pd/CeO2 catalysts during three-way catalysis was examined in real time with operando multi-probe analysis using a micro gas chromatograph, a NO x meter, and a quadrupole mass spectrometer and time-resolved quick X-ray absorption spectroscopy (XAS) measurements. With additional ex situ NO pulse measurement, the results demonstrated the effect of oxygen storage materials under ideal automobile exhaust conditions, which can be summarized into a well-known anchoring effect of CeO2 on active metal species, an oxygen storage/release effect to maintain near stoichiometric conditions on the catalyst surface, NO reduction ability of CeO2 itself, and storage/release of carbonaceous species on/from CeO2 .